Multidimensional Platform Design - Veiga, André; Weyl, E. Glen; White, Alexander (American Economic Review, 2017)
Successful platforms attract not just many users, but also those of the right kind. 'The right kind of user' is one who can either be directly monetized or who differentially attracts other valuable users. Bonacich centrality on the network of user sorting with direct value of monetization captures this feedback loop and thus characterizes the value of user characteristics. We use this value to determine optimal steady-state platform design and reliable means for platforms to reach such a steady state. We apply these results respectively to explain the dynamic growth strategy of social networks and urban development policies of cities.